UiTM towards big data adoption / Zuria Akmal Saad and Siti Norbaini Sarmin - Akmal Saad, Zuria; Sarmin, Siti Norbaini (Universiti Teknologi MARA Cawangan Pahang, 2021)
The objective of this paper is to review the readiness of UiTM towards Big Data (BD) implementation. In the era of the Industrial Revolution 4.0, more organizations are moving towards BD analytics, including the education sector. Datafication of education, which comes from the diversity of systems and practices, has great significance when analyzed. Numerous data in higher education will be useful for the university in planning for future direction. However, past study has discovered that most of the data collected are only for reporting purposes, and some of it are not even used. Thus, this study attempts to review the readiness of UiTM according to the recent five critical success factors of BD which are the organization, people, technology, data management, and governance. The findings of this paper will reveal the progress of BD at UiTM and access the level of the implementation and the action taken to ensure the successful implementation of BD in university environments.